Multidisciplinary consensus-based statement on the current role of middle meningeal artery embolization (MMAE) in chronic SubDural hematoma (cSDH) - J. Bartek; A. Biondi; V. Bonhomme; L. Castellan; G. Catapano; M. Cenzato; G. Di Nuzzo; E. De Robertis; F. Giordano; C. Iaccarino; Z. Kulcsar; M.A. Möhlenbruch; et al. (Brain and Spine)
Introduction: Middle Meningeal Artery Embolization (MMAE) in patients with chronic SubDural Hematoma (cSDH) is a novel treatment approach, albeit the specific role of MMAE in the treatment of cSDH is not yet defined. Research question: The aim of this work is to provide a consensus-based statement from a multidisciplinary panel on the current role of MMAE in patients with cSDH. Materials and methods: A literature search was performed using the keywords MMAE and cSDH. Based on the available published data, the panel was asked if a consensus could be reached on the role of MMAE in both de novo as well as in recurrent cSDH. Results: The panel reached a consensus on the current role of MMAE in both de novo- and recurrent cSDH, as well as in patients on antithrombotics and those with coagulopathy. MMAE should be considered in the following scenarios: 1) As “stand-alone” treatment in de novo cSDH requiring intervention but where surgery is prevented due to either coagulopathy or in patients on antithrombotics in whom the risk of suspension is considered unacceptably high, 2) as “stand-alone” treatment in recurrent cSDH requiring intervention but where surgery is prevented due to either coagulopathy or in those on antithrombotics in whom the risk of suspension is considered unacceptably high and 3) as “adjunct to surgery” in all recurrent cSDH. Discussion and conclusion: This statement is to be considered an expert consensus opinion of delegates representing key international medical societies of specialists involved in the care of cSDH patients.